Pengaruh Job Insecurity Terhadap Turnover Intention - Muhammad Iqbal Nurfauzan; Ii Halilah (Jurnal Riset Bisnis dan Investasi, 2017)
This study aims to determine how the image of job insecurity, turnover intention, and influence of job insecurity on turnover intention in PT Sandy Globalindo. The method used in this research is a descriptive method, while the data collection techniques are interviewing and distributing questionnaires to 101 respondents who were determined by simple random sampling. Based on the research that has been done, regression equation is Y = 26 543 + 0,398X. The study states that in PT Sandy Globalindo, job insecurity and turnover intention have a positive relationship was at 0.464 and job insecurity influence turnover intention of 21,5%.